Meaning and trade in some early modern Spanish and English emblems 1 - López-Peláez Casellas, Jesús (Nordic Journal of English Studies, 2017)
Early modern emblems are based on the commerce between verbal and visual expression. By ‘commerce’ here I mean the dynamic relationship established within the emblem’s triplex, ie, image (pictura) and text (inscriptio and subscriptio), the meaning of which the reader has to negotiate. But commerce and negotiation also were, in their economic sense, topics of various English and Spanish emblems from the late 16th and early 17th centuries, by authors such as Whitney, Wither, Mendo or De Soto. In this article I will deal with commerce in this double way, trying to emphasize how emblems, through their typical combination of image and text, dealt with the different ways in which this other ‘commerce’—early modern trade in the